Evaluasi Kebijakan Penyelenggaraan Haji dan Dampaknya Terhadap Pengeluaran Pemerintah Indonesia Tahun 2023 - anas, Khoiruddin; Nurhayati, Wina; Aslichah (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The pilgrimage to Mecca, known as Hajj, is a significant religious obligation for Muslims around the world. Indonesia, with its large Muslim population, annually sends a substantial number of pilgrims to perform Hajj. This study conducts an evaluation of the policy regarding the organization of Hajj and assesses its implications on the government expenditure of Indonesia for the year 2023. The evaluation focuses on the efficiency, effectiveness, and financial sustainability of the current policy, considering factors such as Hajj quota management, transportation, accommodation, and associated services. The study aims to provide insights into how the Hajj policy impacts the Indonesian government's fiscal allocation and overall budgeting, shedding light on potential areas for improvement and optimization of resources in the future. The findings of this research contribute to better policy formulation and decision-making processes, ultimately aiming to enhance the overall management of Hajj and optimize government expenditure.